Persepsi Mahasiswa Tentang Penggunaan Web Design sebagai Model Pembelajaran Jarak Jauh Selama Pandemi di Perguruan Tinggi Aceh Barat - Veni Nella Syahputri; Endah Anisa Rahma; Nellis Mardhiah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Based on data from the Central Statistics Agency (BPS), especially in Aceh, it was recorded that 4 thousand children were not able to effectively absorb material from teaching staff during the pandemic period (BPS Aceh, 2020). Therefore, the teaching staff needs to pay attention to the development of creative innovative distance learning models so as to increase the interest of students to keep interacting throughout the lesson hours. One method of distance learning that is believed to be able to increase student interest in learning is a web design designed by the teacher to be as attractive as possible so that students can easily access and study learning materials. The purpose of this study was to see the effectiveness of the Development of Distance Learning Models during the Pandemic with a Life Skills-Based Web Design Approach to i-students in West Aceh District. The subjects of this research are university students in West Aceh, namely Teuku Umar University students, STAIN Dirundeng and STIKIP Bina Bangsa Meulaboh. Participants were selected by purposive sampling so that there were 5 students from each campus. The results showed that most partisipants from three Universities in Aceh Barat responded positively to the use of Web Design as Distance Learning Method. Besides, the result from interview with them, there were four obstacles in distance learning, which are (1) the insufficient knowledge of technologi, (2) Internet signal problem, (3) lack of financial to get the internet quota, anda lastly, (4) unsatisfied material understanding from lecturer because of virtual learning.Keywords: Disctance Learning; Web Design Method